PELATIHAN PENGGUNAAN GOOGLE FORM DALAM PENGUMPULAN DATA STUNTING DI DESA DAYEUHKOLOT KABUPATEN SUBANG - Marliana, Reny Rian; Roshafara, Fauziah; Suliadi, Suliadi; Faladiba, Muthia Nadhira (LPPM Universitas Sangga Buana, 2024)
Stunting is a significant threat to the development of future generations' quality in Indonesia, as it can hinder children's growth, reduce learning abilities, and increase the risk of chronic diseases. Therefore, stunting prevention must be carried out through monitoring, starting from the village as the frontline. Dayeuhkolot Village in Subang Regency is one of the villages in West Java Province with a relatively low stunting rate. This success is closely linked to the monitoring efforts carried out by the Human Development Cadres (KPM) in the village. One of the primary responsibilities of KPM is to report data on monitoring the prevention and reduction of stunting. However, the data reporting process still relies on conventional methods, such as paper-based records, which create difficulties in archiving, data recapitulation, and report access. To address these challenges, the utilization of information technology, in accordance with Law No. 23 of 2006, is essential. Google Forms, a user-friendly information technology tool, offers an effective solution. By using Google Forms, stunting data can be collected in real-time and accessed online by relevant stakeholders. Therefore, this community service project was conducted using a science and technology diffusion method, aiming to provide outreach and training on the use of Google Forms for collecting monitoring data on stunting prevention and reduction in Dayeuhkolot Village. The outcomes of this activity show an improvement in the participants' ability to utilize information technology, and the use of Google Forms has proven to overcome the challenges faced by conventional data collection methods.